Investigating the Signalling and Function of C5aR2 - Wright, Oliver (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2023)
Complement component 5a receptor 2 (C5aR2) is an enigmatic receptor for anaphylatoxin C5a. It was initially thought to be a decoy receptor, competitively binding to C5a to negatively regulate C5aR1 signalling. However, recent research has revealed various and conflicting examples of pro-inflammatory and anti-inflammatory effects of C5aR2. Most recently, studies on primary human monocyte-derived macrophages have demonstrated that C5aR2 negatively regulates C5aR1-driven ERK1/2 phosphorylation and suppresses PRR-induced cytokine secretion. However, the literature remains inconsistent, there are limited tools with which to study C5aR2, and the molecular mechanisms underlying the immunomodulatory function of C5aR2 remain largely unexplored. This project aimed to investigate the function and signalling of C5aR2 in macrophages. Initial experiments aimed to validate the effect of C5aR2 agonists P32 and P59 on C5aR1-induced ERK1/2 phosphorylation. P32 and P59 lacked activity in these experiments, therefore novel monoclonal C5aR1 knockout (KO) and C5aR2 KO THP-1 cell lines were generated using CRISPR-Cas9. KO cell lines were characterised using PCR, DNA sequencing and flow cytometry. To investigate immunomodulatory functions of C5aR2, a panel of PRR ligands was used to stimulate WT, C5aR1 KO and C5aR2 KO THP-1 cells, and cytokine secretion was assessed using immunoassays. Use of agonists and antagonists of the cGAS-STING pathway demonstrated that STING-induced IFN-? secretion was significantly increased in C5aR2 KO THP-1 cells and primary human monocyte-derived macrophages. Western blotting demonstrated that expression of cGAS-STING pathway proteins was increased in C5aR2 KO THP-1 cells. Finally, RNAseq revealed that key antiviral signalling pathways were up-regulated in C5aR2 KO cells. Significantly regulated genes and pathways were identified, further characterising the antiviral phenotype of C5aR2 KO cells and providing direction for future work. These results indicate that C5aR2 is a signalling receptor with unique immunomodulatory functions, and suggest that C5aR2 is a negative regulator of antiviral signalling in macrophages. By further characterising the molecular mechanisms underpinning the function of C5aR2, future work could explore its therapeutic potential in inflammatory and infectious disease.
APPROVED
Keywords: STING; antiviral; RNAseq; Complement; Innate immunity; C5aR2; cGAS